Bmi1 regulates stem cells and proliferation and differentiation of committed cells in mammary epithelium - Pietersen, Alexandra M; Evers, Bastiaan; Prasad, Asheeta A; Tanger, Ellen; Cornelissen-Steijger, Paulien; Jonkers, Jos; van Lohuizen, Maarten (Current biology, 2008)
PolycombGroup (PcG) proteins are epigenetic silencers involved in maintaining cellular identity, and their deregulation can result in cancer [1]. Mice without the PcG gene Bmi1 are runted and suffer from progressive loss of hematopoietic and neural stem cells [2-4]. Here, we assess the effects of Bmi1 on stem cells and differentiation of an epithelial tissue in vivo. We chose the mammary gland because it allows limiting dilution transplantations [5, 6] and because Bmi1 is overexpressed in breast cancer [7, 8]. Our analyses show that Bmi1 is expressed in all cells of the mouse mammary gland and is especially high in luminal cells. Loss of Bmi1 results in a severe mammary-epithelium growth defect, which can be rescued by codeletion of the Ink4a/Arf locus or pregnancy. Even though mammary stem cells are present in the absence of Bmi1, their activity is reduced, and this is only partially due to Ink4a/Arf expression. Interestingly, loss of Bmi1 causes premature lobuloalveolar differentiation, whereas overexpression of Bmi1 inhibits lobuloalveolar differentiation induced by pregnancy hormones. Because Bmi1 affects not only mammary stem cells but also more committed cells, our data warrant a more detailed analysis of the different roles of Bmi1 in breast-cancer etiology.